Group Recommendations: Survey and Perspectives - Kompan, Michal; Bielikova, Maria (Computing and Informatics, 2014)
The popularity of group recommender systems has increased in the last years. More and more social activity is generated by users over the Web and thus not only domains as TV, music or holidays are used and researched anymore for group recommendation, but also collaborative learning support, digital libraries and other domains seems to be promising for group recommendation. Moreover, principles of group recommenders can be used in order to overcome some single user recommendation shortcomings, such as cold start problem. Numerous group recommenders have been proposed, they differ in application domains which are specific in group characteristics. Today's group recommenders do not include and use the power of social aspects (group structure, social status etc.), which can be extracted and derived from the group. We provide a survey of group recommendation principles for the Web domain and discuss trends and perspectives in this field.